2017
DOI: 10.1002/rcm.7928
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous regiochemical assignment of sulfoquinovosyl mono‐ and diacylglycerols in parsley and spinach leaves by liquid chromatography/electrospray ionization sequential mass spectrometry assisted by regioselective enzymatic hydrolysis

Abstract: The predominant sulfolipid in leaf extracts of raw parsley (Petroselinum crispum) and spinach (Spinacia oleracea) was identified as SQDG 18:3/16:0, along with SQMG 18:3/0:0 and SQMG 16:0/0:0. The present CID-MS-based method can be considered a successful approach to validate the regiochemical characterization of sulfolipids paving the way for their unambiguous characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
4
14
0
Order By: Relevance
“…The results of the cellular and chloroplast lipid composition in I. galbana Parke indicated that chloroplasts were the major sites for fatty acid synthesis and lipid biosynthesis. The results of glycolipids were consistent with those reported for chloroplast from land plants like Arabidopsis [46,47]. One important exception was that the content of DGDG was higher compared with the MGDG in this alga.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the cellular and chloroplast lipid composition in I. galbana Parke indicated that chloroplasts were the major sites for fatty acid synthesis and lipid biosynthesis. The results of glycolipids were consistent with those reported for chloroplast from land plants like Arabidopsis [46,47]. One important exception was that the content of DGDG was higher compared with the MGDG in this alga.…”
Section: Discussionsupporting
confidence: 89%
“…Due to the occurrence of a sulfonic group in their structure, SQMG like SQDG could be easily detected as deprotonated species ([M-H] − ) using ESI in negative polarity [27]. As already reported [31,32], it is possible to recognize both SQDG and SQMG species from their tandem mass spectra, thanks to a marker product ion at m/z 225.01, corresponding to the dehydrated form of the sulfoquinovosyl anionic head with molecular formula [C 6 H 9 O 7 S] − . Since each acyl chain generates two product ions, one due to its neutral loss as fatty acid (the neutral loss as ketene is hardly revealed) and the other to the corresponding carboxylate anion, it is possible to infer both the length and unsaturation degree of the fatty acyl chain(s) of SQDG and SQMG [27,31,33].…”
Section: Sqdg and Sqmg In The Lipid Extract Of U Pinnatifida By Rplc-esi(-)-ms And Tandem Ms Analysismentioning
confidence: 99%
“…In another case, by combining the hydrolysis catalyzed by Lecitase® Ultra and reversed-phase liquid chromatography with electrospray ionization and sequential mass spectrometry, the regiochemistry of sulfoquinovosylmonoglycerides and sulfoquinovosyldiglycerides in the lipid contained in spinach (Spinacia oleracea) and parsley (Petroselinum crispum) was investigated and the main components determined [155].…”
Section: Other Uses Of Lecitase Ultra In Foodmentioning
confidence: 99%